Islamic perspective of myths rooted in studio culture - Abdullah, Fadzidah (Kulliyyah of Architecture, International Islamic University Malaysia, 2011)

(untitled)
This paper is part of literature review carr:ied out for a research on Studio Culture, specifically discussing on Islau-ric perspective of uryths rooted in Studio Culture. ln architectural education. Studio culture was -eenerally developed in westem arclritecture scl.rools u ith secular rnethodological consideratior.r arrd then adapted by schools of architecture irr various Islarr.ric countries. Studio Culture is shrouded il'ith mytlis that are considered necessary for arciritectural students to conform in order to be successful architects. This researcl.t has the objective of evaluating the appropriateness of embracing the myths, based on Islamic perspectives. Tliis research is an example of multidisciplinary research tl.rat combined the fields of arclritectural education and Islamic perspective of education. By critically analysing this issue, it is hoped that this research could benefit alchitecture students and academicians, as rvell as architectural practice in general.